The Impact of Financial Difficulties, Environmental Uncertainty, and Managerial Compensation on Tax Avoidance (An Empirical Research on Energy Sector Companies Listed on Indonesian Stock Exchange from 2019 to 2023) - Asri Utami; Intan Rahma Sari (MultiTech Publisher, 2025)
This research aims to test and provide empirical evidence of the influence of financial difficulties, environmental uncertainty and management compensation on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. This type of research is quantitative research and uses secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange (BEI). The population in this research is 74 energy sector companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. The sampling technique used a purposive sampling method and obtained 13 sample companies over a 5 year period so that the data analyzed amounted to 65 data. The analysis technique used is logistic regression with the help of the eviews 12 program. The research results show that simultaneously financial difficulties, environmental uncertainty and management compensation have a significant effect on tax avoidance. Meanwhile, partially financial difficulties have a significant effect on tax avoidance, but environmental uncertainty and management compensation do not have a significant effect on tax avoidance.